Community Pharmacists' Knowledge on Cancer and Screening Methods - TEZCAN, SONGÜL (SAGE PUBLICATIONS LTD, 2022)
Background and Objective The aim of the study is to evaluate the knowledge of community pharmacists on cancer and screening methods. Setting and Method This study was a descriptive cross-sectional study and was conducted between January-June 2020 in Istanbul/Turkey. a structured questionnaire was applied to pharmacists as online. The questionnaire was prepared by the researchers and consisted of 49 questions; basic information about cancer (15 items), signs and symptoms (11 items), causes and risk factors (14 items), cancer screening methods (9 items). Results It was determined that the majority (>90%) of the pharmacists did not receive any education on cancer and/or cancer screening methods after graduation. The sufficient knowledge level of the pharmacists about cancer basics, signs and symptoms, and risk factors were found to be as 80%, 77%, and 67%, respectively. The internal consistency level of the questionnaire was calculated (Cronbach's alpha = 0.814). The item Every woman should perform breast self-examination and notify a health professional when there is a change in breast appearance or feeling, was answered correctly by 98% of the pharmacists. It was determined that 71% of the pharmacists gave the correct answer to the item Women aged 21-30 years should have a PAP smear every 3 years. Conclusion According to the results of the study, while the rate of sufficient knowledge level on cancer was found to be low, knowledge on cancer screening was found to be sufficient. We think that pharmacists should receive training on cancer and screening methods and to follow the guidelines closely.
Keywords: Community pharmacist; knowledge; cancer; cancer screening; Turkey; EDUCATION; BARRIERS